Linha de montagem para a produção de habitações em light steel frame : projeto e otimização - Vivan, André Luiz (2016)
The Construction Industry (CI), regarding the production of single-family housing in Brazil, is still characterized by the use of techniques and technologies that are highly dependent on knowledge and manpower experience. Thus, in most projects involving the construction of single-family housing, there are handcraft features when the building site is understood as a production system. Thus, it is common to observe the pathological manifestations appearance in post-occupational analysis, in addition to non-compliance with deadlines and budgets. In this sense, this thesis suggests that the CI breaks with some technical and cultural paradigms from the use of an industrialized building system, such as Light Steel Frame (LSF) and from the use of assembly lines, focusing the industrialization of singlefamily housing production. This proposal is based on four steps involving theoretical and experimental approaches. The theoretical approaches involved the structuring of a systematic literature review, which were identified gaps in scientific knowledge and the research hypothesis, besides the development of basic theoretical framework, the product definition and production system design. The experimental approach was represented by activities related to computer simulation of the production system and its subsequent optimization. The computer simulation was performed with the ProModel® software where was simulated the production of five hundred housing units from the programming logic of the designed system. Seven scenarios were simulated, with the results of its simulation it was possible to identify the most efficient configuration from optimizing the use of some resources, identified by layout B. In addition, the main results of the simulations show that it is possible to assembly the housing unit designed at 11.14 hours, with a cycle time of 5.56 hours, with the settings of scenario seven. The purpose of this thesis and the results can be considered relevant because promote innovation for both the consumer market and to the academy, since it deals with concepts little used or known in the CI. It also enables greater speed and volume of production, facing the Brazilian housing deficit, with significant quality improvements.